Enacting Environmental Justice Through the Undergraduate Classroom: The Transformative Potential of Community Engaged Partnerships - Gwen D'Arcangelis; Brinda Sarathy (The University of Alabama, 2022)
In this paper, we document our efforts, as activist scholars, to cultivate among our liberal arts students a critical environmental justice consciousness through engaging with community organizations. We detail our efforts to make the classroom a space in which to engage environmental justice beyond a narrow and short-term focus on the disproportionate impact of environmental harms in low-income and minority communities to a more expansive and consistent attention to histories of inequality and processes of marginalization. We argue that community engaged partnerships afford opportunities for educators to combine theory with practice and disrupt students' assumptions about what or who constitutes the environment. Our socially privileged students, in gaining a better understanding of structural/historic privilege and how their own positionality implicates them in environmental injustice, have been able to re-evaluate and reframe their political and theoretical commitments and carve out meaningful ways to contribute to environmental justice work.